METHOD OF SELECTION FOR TOLERANCE TO SOIL WATERLOGGING IN MAIZE PLANTS - PORTO, MARILDA PEREIRA (1997)
Most of the cultivated species (crops and forrages) is damaged by the lack of or low availability of oxigen in the soil, a consequence of the water filling of the macropores. The arca of the low plains of Brazil Southem Region (Rio Grande do Sul, Santa Catarina and Parana States) is approximately 6.8 millions hectares and most of these soils is dedicated to irrigated rice crop. The main characteristic of these soils is hydromorphism. The excess of humidity is associated with a water table neer the soil surface, as a result of the plain relief and of an impermeable B horizon, both impairing natural drainage atter excessive rainfall. Reaction of maize planta to water excess in the soil have already been evaluated and breeding methods are being employed to develop tolerant germplasrn. This work presents a simple methodology, easy to carry out, that is useful to select maize plantlets (20 days old) tolerant to soil waterlogging, through the examination of their root systems. The determinations of density and of volumetric and gravimetric humidities on 160 cm' of soil contained in plastic cups, compared with field collected data (Albaqualf) allowed to infer that the "cups method" is adequate to be used in screening young maize planta tolerant to excessivo soil water.